2020
DOI: 10.1186/s12912-020-00503-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of nurse practitioners, physician assistants and other nursing staff in HIV pre-exposure prophylaxis care in the United States: a systematic review and meta-analysis

Abstract: Background Although pre-exposure prophylaxis (PrEP) was approved for primary HIV prevention by the Federal Drug Administration in 2012, PrEP utilization has been suboptimal. A body of literature and programs has emerged to examine the role of nurse practitioners (NPs), physician assistants and nursing staff in PrEP care. This review aims to understand the current status of non-physician health providers in PrEP care implementation in the United States. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 33 publications
0
25
0
1
Order By: Relevance
“…However, awareness of strategies such PrEP have been found to be lower among NPs than among physicians. 8 Although completion of the NHC only had a small effect on students' intent to working with PLWH, this may be due to the perception that PLWH are referred to specialty clinics for management of their HIV diagnosis and co-occurring conditions. Students may have not viewed HIV care on a continuum where PLWH also need primary care services such as immunizations and management of other acute and chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, awareness of strategies such PrEP have been found to be lower among NPs than among physicians. 8 Although completion of the NHC only had a small effect on students' intent to working with PLWH, this may be due to the perception that PLWH are referred to specialty clinics for management of their HIV diagnosis and co-occurring conditions. Students may have not viewed HIV care on a continuum where PLWH also need primary care services such as immunizations and management of other acute and chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The need for standardized HIV education in NP programs is further highlighted by persistent gaps in knowledge related to HIV prevention including testing behaviors and pre-exposure prophylaxis (PrEP) among NPs. 8,11 In an effort to address these providers' gaps in knowledge, the AIDS Education and Training Center Program, in collaboration with the University of Washington and Health Resources and Service Administration (HRSA), developed a National HIV Curriculum (NHC) to address the HRSA national strategic goal of increasing access to care and optimizing health outcomes for PLWH. 12 The primary aim of the NHC is to increase the number of health care professionals who can competently provide care for PLWH by providing up-to-date, evidence-based standardized curriculum related to HIV screening, diagnosis, ongoing treatment, and prevention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 A recent systematic review of studies from the USA concluded that nurses were 40% more likely than doctors to prescribe PrEP. 22 Experience from task sharing of ART shows that clients often prefer receiving care closer to their homes, 23 and that this preference translates into improved retention in care and long-term clinical outcomes when care is decentralised. 5 Task sharing can also improve the cost-effectiveness and efficiency of health systems.…”
Section: Nurse-led Prep Provisionmentioning
confidence: 99%
“…The Kenyan Ministry of Health has named research on pharmacy PrEP as a high priority [39]. Nurse-led PrEP delivery in sexual health services has been trialled successfully in several settings [40,41], and in one study, nurse prescribers were more likely than physicians to prescribe PrEP [42].…”
Section: Promoting Preexposure Prophylaxis As Both Decreasing Risk An...mentioning
confidence: 99%